Competitive vertical integration - Pontes, José Pedro (1993)
In this paper, we assess that sufficient conditions for full vertical integration in a duopoly hold if marginal costs are constant and quantities are strategic substitutes. That is to say: vertical integration by both duopolists is an equilibrium outcome of a non-cooperative game under fairly general assumptions. Two conditions lie behind this result. The first one, is that, if all firms are disintegrated, it pays off for a producer and a distributor to merge unilaterally. The second one, assuming that merging decisions take place sequentially, is that it is profitable for the remaining upstream-downstream firms to follow vertical integration. However, if the firms can reach a binding agreement on vertical structures, they will prefer to remain disintegrated: profit of an integrated firm under full vertical integration is smaller than the sum of producer's and distributor's profits when all firms are disintegrated.